1973
DOI: 10.1042/bj1340879
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of acetamidothiazoles in the rat. 2-Acetamido-4-chloromethylthiazole

Abstract: 2-Acetamido-4-chloromethylthiazole is metabolized in the rat to (2-acetamido-4-thiazolylmethyl)mercapturic acid and 2-acetamidothiazole-4-carboxylic acid. 2-Acetamido-4-methylthiomethylthiazole and the corresponding sulphoxide and sulphone are also produced as minor metabolites. The identification of the metabolites is described and their formation investigated. Quantitative results on the excretion of the metabolites labelled with (14)C are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The sulfur analogue may not isomerize to the analogous methoxy derivative, so that the stable sulfoxide is detected (Figure 7). This is similar to the finding that the antiinflammatory drug 2-acetamido-4-(chloromethyl)thiazole is reported to be excreted as a stable methyl sulfoxide (19).…”
Section: Discussionsupporting
confidence: 87%
“…The sulfur analogue may not isomerize to the analogous methoxy derivative, so that the stable sulfoxide is detected (Figure 7). This is similar to the finding that the antiinflammatory drug 2-acetamido-4-(chloromethyl)thiazole is reported to be excreted as a stable methyl sulfoxide (19).…”
Section: Discussionsupporting
confidence: 87%
“…However, in 1965, Colucci and Buyske showed that benzothiazole-2-sulfonamide is converted in rats, rabbits and dogs in part to 2-mercaptobenzothiazine in which the sulfur of the mercaptan moiety is derived from GSH. Later, Chatfield and Hunter (1973) showed that 2-acetamido-4-chloromethylthiazole is converted in rats to 2-acetamido-4-methylthiomethylthiazole in part through the mercapturate pathway. Earlier, Anderson and Schultze (1965) showed that bovine liver and kidney extracts contain a “C-S” lyase that converts S -(1,2-dichlorovinyl)-L-cysteine (DCVC, the cysteine S -conjugate of trichloroethylene) to pyruvate, ammonia and a reactive chlorine-containing fragment.…”
Section: Discovery Of Cysteine S-conjugate β-Lyases – the Thiomethyl mentioning
confidence: 99%
“…This metabolite was considered to be generated by scission of the methylaminothiazole ring, as reported for other thiazole derivatives which yielded the thioamides (13)(14)(15)(16). The mechanism of metabolic ring-opening of the thiazole of SM-8849 is now under investigation with toxicological interest, for an anti-thyroid action of thiourylene derivatives is well-known (17).…”
Section: L-5512mentioning
confidence: 99%